THE ANALYSIS OF ISLAMIC FAMILY LAW ON PARENTING PATTERNS AT AL-IKHLAS ISLAMIC BOARDING SCHOOL TALIWANG AS A FORM OF CHILD RIGHTS PROTECTION - Nafisah, Fiddha; Tahir, Masnun (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study analyzes the aspects of family law in Islam related to parenting in Islamic boarding schools as a form of protection of children's rights, with a case study at Al-Ikhlas Islamic Boarding School, Taliwang District, West Sumbawa Regency. This research focuses on two main aspects, namely how the parenting style in the Al-Ikhlas Islamic Boarding School is applied and how the Islamic family law analyzes the parenting style. Using a qualitative research approach with empirical methods, data were collected through interviews, observations, and documentation. The results of the study show that the parenting style at the Al-Ikhlas Islamic Boarding School involves 24-hour parenting as a means of education and the implementation of the